Pelatihan Digital Marketing Untuk Peningkatan Kapasitas Perempuan Dalam Pemasaran Produk - Ryan Hamonangan; Riri Narasati; Ai Sri Nurmala; Alfira Ayu Febriaan Lesmana (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The development of digital technology has brought significant changes in the world of education, especially in online learning methods. Digital literacy is an essential skill for educators in navigating technology-based learning. This research aims to improve digital literacy for elementary school teachers in facing online learning challenges. The training program developed includes a basic understanding of digital technology, the use of learning software, and effective teaching strategies in an online environment. The research method used was a qualitative approach with observation, interviews and case studies in several primary schools in Cirebon district. The results showed that digital literacy training significantly improved teachers' competence in using technology and improved the effectiveness of online teaching. Teachers who participated in this training program were able to optimize the use of various digital platforms, improve interaction with students, and adapt the curriculum to better fit the online learning model. In addition, the main challenges faced include limited access to technology infrastructure and lack of adequate technical support. Therefore, more supportive policies in the provision of technology resources and continuous training programs for teachers are needed. The findings of this study confirm that improving digital literacy is a key factor in the successful implementation of online learning at primary school level. By improving teachers' competence in technology utilization, it is expected that the learning process can be more interactive, effective and adaptive to the times. This study also recommends the need to integrate digital-based curriculum so that teachers are better prepared to teach online materials.